Synthetic thiophenes induce chromosomal damage and trigger apoptosis in human cancer cell lines - Filipe N. Franco; Júlia T. Oliveira; Kimberly B. Tecchio; Flaviana A. Santos; Moacyr J.B.M. Rêgo; Francisco J.B. Mendonça-Júnior; Maira G.R. Pitta; Michelly C. Pereira; Rosy I.M.A. Ribeiro; Vanessa J.S.V. Santos; Fabio V. Santos (Elsevier, 2022)
Thiophenes are heterocyclic compounds containing a five-membered ring with sulphur as the heteroatom. This class of substances has been shown to have several biological activities, including specific anti-proliferative effects against some cancer cell lines. The aim of the present study was to evaluate in vitro possible cytotoxic, genotoxic, and mutagenic properties of synthetic thiophenes using cell lines derived from human solid tumours. Different methodologies were employed to assess the cytotoxic effects of the compounds here named SB44, SB83, and SB200 (a 3-[4,5-dimethylthiazol-2-yl]-2,5-diphenyltetrazolium bromide [MTT] assay, clonogenic assay, and annexin V staining) and to elucidate the chromosomal damage possibly involved in the triggered cell death (micronucleus, comet, and γ-H2AX assays). All tested thiophenes reduced cell survival regardless of the dose and duration of treatment. By contrast, compound SB200 manifested an attractive selectivity index towards the tumour cell lines under study. All the evaluated compounds caused chromosomal damage in vitro in the same way. The results imply that these compounds induce cell death by apoptosis as a consequence of chromosomal damage. Taken together, the data suggest that the thiophenes tested herein are useful prototypes for the development of anti-cancer drugs.